Integrating palynostratigraphy with zircon geochronology in the Lower Jurassic Precipice Sandstone and Evergreen Formation to improve stratigraphic correlation within the Great Artesian Basin, Australia. (October 2022) - La Croix, Andrew D.; Sobczak, Kasia; Esterle, Joan S.; Bianchi, Valeria; Wang, Jiahao; He, Jianhua; Hayes, Phil; Underschultz, Jim R.; Garnett, Andrew
Abstract: The Great Artesian Basin (GAB) in eastern Australia is one of the most productive complex aquifers on Earth, covering a large portion of the continent. Yet stratigraphic correlation within and among constituent basins of the GAB remain poorly constrained. This has significant implications for resource estimation and management. In this study and for the first time, palynostratigraphic and zircon geochronologic data are integrated from the Lower Jurassic Precipice Sandstone and Evergreen Formation in the Surat Basin–a component of the GAB. The goal was to better constrain the depositional ages as a starting point for calibrating stratigraphy across the GAB. The results showed that the Precipice Sandstone and Evergreen Formation are highly diachronous, as are their sequence stratigraphic subdivisions. We provisionally revise the stratigraphic framework based on the integration of age information to show that the "lower" Precipice Sandstone (lowstand systems tract) ranges from Hettangian to Pliensbachian, the "upper" Precipice Sandstone (transgressive systems tract) extends from Sinemurian to Pliensbachian, the Evergreen Formation varies from Pliensbachian to Aalenian within which the Boxvale Sandstone varies from Pliensbachian to Toarcian and the Westgrove Ironstone member ranges from Pliensbachian to Aalenian. Additionally, the data allow us to provisionally assign the APJ1 to APJ2 palynozone boundary to ∼190 Ma, the APJ3.2 to APJ3.3 boundary to ∼180 Ma, and to constrain the APJ2.2.2 palynozone to span 184.80 ± 0.20 Ma. This new age-context for the Precipice Sandstone and Evergreen Formation will be useful for future workers correlating strata between constituent basins of the GAB, as well as New Zealand and the broader Gondwana palaeocontinent. Highlights: Integration of palynostratigraphic and zircon geochronologic datasets from the Lower Jurassic System in eastern Australia. Precipice Sandstone and Evergreen Formation in Surat Basin are diachronous, as is their (current) sequence stratigraphy. Provisional palynozone boundaries are provided based on age-control. Updated lithostratigraphic and sequence stratigraphic age ranges are provided. Important implications for resource estimation, water management, and correlation across Gondwana.